2020
DOI: 10.1111/jdv.16234
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface disease during dupilumab treatment in patients with atopic dermatitis, is it possible to prevent it?

Abstract: 6 Chinese Clinical Trial Register [Internet]. A randomized, blinded, controlled, multicenter clinical trial to evaluate the efficacy and safety of Ixekizumab combined with conventional antiviral drugs in patients with novel coronavirus pneumonia (COVID-19). Changsha (Hu'nan): Ministry of Health (China), 2020. Identifier ChiCTR2000030703.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Furthermore, Pistone et al reported no DIOSD in a series of 30 patients treated with dupilumab for 6 months. 55 Indeed, they concomitantly administered artificial tears twice daily, immediately after dupilumab initiation, which might have prevented or delayed the onset of DIOSD. Additionally, Fukuda et al showed improvement in two cases of atopic keratoconjunctivitis with giant papillae after dupilumab treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Pistone et al reported no DIOSD in a series of 30 patients treated with dupilumab for 6 months. 55 Indeed, they concomitantly administered artificial tears twice daily, immediately after dupilumab initiation, which might have prevented or delayed the onset of DIOSD. Additionally, Fukuda et al showed improvement in two cases of atopic keratoconjunctivitis with giant papillae after dupilumab treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…From the 155 cases presented in the series, [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] 12 discontinued dupilumab due to DIOSD severity. Most of the cases were diagnosed by an ophthalmologist (63%), [46][47][48][49][50][51][52]54,56,57,60 the rest being assessed by a dermatologist.…”
Section: Case Seriesmentioning
confidence: 99%
See 3 more Smart Citations